A novel LightGBM-LSTM-GA framework for performance degradation prediction of composite laminates with variable structural parameters - Xin He; Datong Liu; Huizhen Hua; Hua Zhang; Yafei Xu (Engineering Structures, 2026)

Seasonal source shifts and toxicity implications of PM2.5-bound polycyclic aromatic hydrocarbons in central China: The critical role of underrated local emissions - Runqi Zhang; Sheng Li; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Pollution Research, 2026)

SIRT5 Attenuates Doxorubicin-Induced Acute Cardiac Injury by Modulating PHB2 Succinylation and the Mitophagic Response - Aihui Zeng; Haiqiong Liu; Xudong Song; Jing Yan; Yan Zhou; Datong Sun; Aihua Chen (Cardiovascular Toxicology, 2026)

Development and characterization of a novel compensating wheat–Dasypyrum villosum interstitial translocation line Dv6-IT1 carrying the powdery mildew resistance gene PmV - Renhui Zhao; Wentao Wan; Man Xu; Tiantian Chen; Ling Wang; Ronglin Wu; Shujiang Zang; Zunjie Wang; Wei Jiang; Datong Liu; Yong Zhang; Xiue Wang; et al. (Theoretical and Applied Genetics, 2026)

Field observations reveal biomass burning and cooking as the significant sources of PM2.5-bound organic acids in Central China - Ziyue Xiang; Runqi Zhang; Sheng Li; Bin Xu; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Environment, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

A colorimetric and electrochemical dual-mode sensor based on the morphological evolution of Au@Ag nanostars for quantitative silver ion detection - Junyao Li; Yujie Wang; Ling Cai; Zheyuan Lin; Zhengxiao Jiang; Peiming Liu; Wenrong Cai; Datong Wu; Zheng-Zhi Yin; Yong Kong (Journal of Environmental Chemical Engineering, 2025)

Hazardous mode and vibration source identification based on the rigid-flexible coupled model: An application on AUVs powertrain - Dingchang He; Yonggang Liu; Jing Wei; Datong Qin; Yi Zhang (Ocean Engineering, 2025)

Impact of Open Crop Straw Biomass Burning Emissions on the Air Pollution in the Hunan Province, China: A Case Study - Datong Luo; Lin Luo; Na Wang; Jianxun Wu; Lang Liu (Aerosol Science and Engineering, 2025)
Emissions from open crop straw burning (OCSB) during crop harvest have exerted considerable impacts on the air quality in China, but the quantitative evaluation of OCSB to air pollutants remains insufficient. In the study, the WRF-Chem model is used to quantitatively evaluate the impacts of OCSB on the air quality in Hunan, China from October 15 to 26, 2024. During the study episode, OCSB contributes 45.7% and 16.8% of the anthropogenic emission of organic carbon and non-methane volatile organic compounds, respectively. Model simulations show that OCSB emissions account for 2.8% of the maximum daily 8-hour average ozone (MDA8 O 3 ) concentration, but play a more substantial role in particulate pollution, contributing 25.6% to near-surface fine particulate matter levels. OCSB is an important organic aerosol (OA) source, increasing primary OA by 46.2% and secondary OA by 62.7%. The enhanced OA accounts for 54.8% of the total PM 2.5 increase induced by OCSB emissions. Sensitivity experiments show that the concentrations of aerosol species generally decrease linearly with reduced OCSB emissions, while MDA8 O 3 concentrations exhibit a non-linear trend due to the complex responses to its precursors. Implementing the clean disposal of straw residue during crop harvest presents an effective strategy to improve the air quality in Hunan.

Optimizing N rate in wheat-maize rotation to match long-term and inter-seasonal N turnover for high yield and sustainability using STICS - Datong Zhang; Shuaijie Shen; Zhiyuan Bai; Matthew Tom Harrison; Ke Liu; Robert M. Rees; Cairistiona F.E. Topp; Jun Zou; Yuhao Yang; Zhenwei Song; Haotian Chen; Xiaogang Yin (Field Crops Research, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Preparation of the sandwiched PS-SiO2-PVAc-SiO2 electrospinning fiber membrane with super-hydrophobic and self-cleaning and its performance in oil-water emulsion separation - Yang Hu; Xiaoyan Lin; Datong Liu; Lili Liang; Chunxia Pang; Xunhai Pan (Journal of Environmental Chemical Engineering, 2024)

Data-driven cloud-based intelligent gear-shift decision strategy of vehicle considering driving behavior and environment - Jihao Feng; Datong Qin; Yonggang Liu; Dongye Sun; Zheng Guo (Journal of Cleaner Production, 2023)

Intermediate-volatility aromatic hydrocarbons from the rubber products industry in China - Zhou Zhang; Yanli Zhang; Lilin Zou; Zhongxiangyu Ou; Datong Luo; Zhan Liu; Zhonghui Huang; Leilei Fei; Xinming Wang (Science of The Total Environment, 2023)

Compensatory thalamocortical functional hyperconnectivity in type 2 Diabetes Mellitus - Jie Wang; Shanlei Zhou; Datong Deng; Mimi Chen; Huanhuan Cai; Cun Zhang; Fujun Liu; Wei Luo; Jiajia Zhu; Yongqiang Yu (Brain Imaging and Behavior, 2022)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)